Oral pemphigus vulgaris with one year follow-up and complete remission - Dineshkumar Thayalan; Rajkumar Krishnan; Rameshkumar Annasamy; Priyadharsini Nataraj; N. Indumathi (Oral Oncology Reports)
Pemphigus vulgaris is a chronic autoimmune disorder that usually presents with blister formation which are mucocutaneous in nature that causes excruciating erosions. Although the cause of the illness is still unknown, Bulla development and intraepithelial clefting are caused by the autoantibody immunoglobulin (Ig) G directed against the glycoproteins desmoglein (Dsg) 3 and desmoglein 1. Patients typically exhibit bullae, vesicles, or erosions of the skin or mucous membranes. As ulcers in the oral cavity cause excruciating pain and dysphagia, there's a greater likelihood that the condition will be mistakenly diagnosed as viral infections or erythema multiforme (EM). Correlations between clinical, histological, and immunopathological data are necessary for proper diagnosis and prompt therapy.